Optimisation of non-thermal ultrasonication process for retaining nutritional quality in cow milk: Effects of fat percentage and treatment parameters - Nurul’azah Mohd Yaakub; Chin Nyuk Ling; Norliza Julmohammad; Nantawan Therdthai; Alifdalino Sulaiman (HH Publisher, 2024)
The thermal unit operation used in milk processing causes changes in milk nutritional quality. Hence, optimising the non-thermal ultrasonication process at 25°C can be a potential method to retain milk quality. The objective of this research is to optimise the ultrasonication process of standardised fresh cow's milk at various fat percentages and elucidate its effect on nutritional values using response surface methodology (RSM). A central composite design based on fat (1–4%); ultrasound amplitude (10–70%), and sonication time (1.5–10.5 min) was used. Data analysis shows that the ultrasonication process significantly (p<0.05) affects the percentage of fat, free fatty acid (FFA), protein, solid nonfat; solid non-fat (SNF), lactose, casein, and total solid (TS). The adjusted R 2 for fat, free fatty acid, and TS with goodness-of-fit were 0.940, 0.975, and 0.955, respectively. The generation of FFA in raw cow milk was observed with some ultrasonication conditions. As a conclusion, the processing parameters to get the highest fat and lowest FFA is a combination of 4% milk fat, 10% amplitude, and 1.95 min sonication time with 46.8 J/mL energy density can be applied to control the release of further FFA generation from the milk processing line.